2012
DOI: 10.1038/cddis.2012.176
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 analogues: critical issues on the specificity, activity and in vivo use in experimental disease models

Abstract: Necrostatin-1 (Nec-1) is widely used in disease models to examine the contribution of receptor-interacting protein kinase (RIPK) 1 in cell death and inflammation. We studied three Nec-1 analogs: Nec-1, the active inhibitor of RIPK1, Nec-1 inactive (Nec-1i), its inactive variant, and Nec-1 stable (Nec-1s), its more stable variant. We report that Nec-1 is identical to methyl-thiohydantoin-tryptophan, an inhibitor of the potent immunomodulatory enzyme indoleamine 2,3-dioxygenase (IDO). Both Nec-1 and Nec-1i inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
384
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(406 citation statements)
references
References 49 publications
8
384
2
Order By: Relevance
“…We assessed RIP3 activity by Western blot 10 hours after incubation with sCD74/rMIF and observed a 2‐fold increase of RIP3 phosphorylation compared with untreated control (control versus sCD74/rMIF: 100% versus 222.2±45.98%; P =0.0376, d =1.88), whereas neither rMIF nor sCD74 treatment alone affected phospho‐RIP3 levels (Figure 2C and 2D). To confirm that necroptosis contributes to cell death induction, we blocked activity of RIP1, the upstream kinase of RIP3, with the pharmacological inhibitor, 7‐Cl‐O‐Nec1 (Nec1s) 54. Surprisingly, Nec1s‐pretreated myofibroblasts demonstrated a small, but significant, decrease in cell viability following MIF treatment compared with control cells (Nec1s/control versus Nec1s/MIF: 99.72±3.04% versus 79.62±4.63%; P =0.025, d =1.81).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed RIP3 activity by Western blot 10 hours after incubation with sCD74/rMIF and observed a 2‐fold increase of RIP3 phosphorylation compared with untreated control (control versus sCD74/rMIF: 100% versus 222.2±45.98%; P =0.0376, d =1.88), whereas neither rMIF nor sCD74 treatment alone affected phospho‐RIP3 levels (Figure 2C and 2D). To confirm that necroptosis contributes to cell death induction, we blocked activity of RIP1, the upstream kinase of RIP3, with the pharmacological inhibitor, 7‐Cl‐O‐Nec1 (Nec1s) 54. Surprisingly, Nec1s‐pretreated myofibroblasts demonstrated a small, but significant, decrease in cell viability following MIF treatment compared with control cells (Nec1s/control versus Nec1s/MIF: 99.72±3.04% versus 79.62±4.63%; P =0.025, d =1.81).…”
Section: Resultsmentioning
confidence: 99%
“…As RT-PCR revealed that both rip1 and rip3 were upregulated in pde6c w59 mutant cone photoreceptors, we took advantage of small-molecule drugs that target specifically RIP1 34 and RIP3 kinases 35 as potential pharmacological approaches to inhibit cone cell death. Using dose-response analysis in wild-type zebrafish, 10 the highest concentration of necrostatin-1s (RIP1 inhibitor) and necrosulfonamide (RIP3 inhibitor) that could be utilized without causing toxicity to embryos was 100 and 20 mM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, existing data that imply protection by interference with necroptosis in various in vivo models used the RIPK1 kinase inhibitor necrostatin (Nec)-1 to inhibit necrotic signaling (10,11,26,27). However, Nec-1 has recently been discussed to directly influence the immune system, besides its effects to block release of CDAMPs (28,29). Therefore, it remains an open question whether necroptosis in IRI is of relevance in the absence of a functional immune system.…”
mentioning
confidence: 99%